IMPLEMENTATION OF CLINICAL SUPERVISION AT STATE ISLAMIC HIGH SCHOOL BINJAI - Aisyah, Siti; Wijaya, Candra; Rohman, Fatkhur (Pena Cendekia Insani, 2025)
This study aims to analyze the implementation of clinical supervision at Madrasah Aliyah Negeri Binjai and its impact on improving teachers' pedagogical competence. Using descriptive qualitative methods, data were collected through observation, in-depth interviews, and documentation studies. The results show that the principal plays an important role in improving teachers' teaching skills through planned training programs, including the preparation of Learning Implementation Plans (RPP) and the use of effective learning media. The systematic clinical supervision process, from planning to evaluation, creates a productive and collaborative learning environment, and optimizes interactions between teachers and the principal. Open communication and emotional support from the principal have been shown to increase teacher motivation and confidence in the teaching process. However, challenges faced include teacher discomfort during the supervision process and the need for adjustments in the implementation of the new curriculum. Recommendations include the development of more focused training programs and increased communication between teachers and management to create a supportive atmosphere, which is expected to provide a positive contribution to the development of education at Madrasah Aliyah and improve the quality of student learning outcomes as a whole.